PROBLEMS AND SOLUTIONS OF USING NEW TECHNOLOGIES IN EDUCATION - Soliev Oybek Sokhibjon ugli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article talks about the technologies that can be used in the educational process, the problems and solutions of its application to the educational process, and the possibilities of using modern technologies to improve the quality of education.